2018
DOI: 10.3390/ijms19010225
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Antagonists Mitigate the Effects of Dioxin on Critical Cellular Functions in Differentiating Human Osteoblast-Like Cells

Abstract: The inhibition of bone healing in humans is a well-established effect associated with cigarette smoking, but the underlying mechanisms are still unclear. Recent work using animal cell lines have implicated the aryl hydrocarbon receptor (AhR) as a mediator of the anti-osteogenic effects of cigarette smoke, but the complexity of cigarette smoke mixtures makes understanding the mechanisms of action a major challenge. 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD, dioxin) is a high-affinity AhR ligand that is frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Variations on the CXCL12 expressions on the cell lines are also seen ( 39 ). Using AhR antagonist, Yun et al ( 40 ) reported that TCDD induced CXCR4 in an AhR dependent manner. These findings indicate that CXCR4/CXCL12 are different mediated according to cells and microenvironments differences.…”
Section: Discussionmentioning
confidence: 99%
“…Variations on the CXCL12 expressions on the cell lines are also seen ( 39 ). Using AhR antagonist, Yun et al ( 40 ) reported that TCDD induced CXCR4 in an AhR dependent manner. These findings indicate that CXCR4/CXCL12 are different mediated according to cells and microenvironments differences.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments in vivo on the rat lines with different sensitivity to TCDD have established both bone malformation (a shorter bone length) and a dose-dependent effect of this change [ 73 ]. Using a mice and rat model of differentiation of tibia stromal medullary cells it was confirmed that the TCDD disrupting action on bone development and regeneration consists in the decrease of the alkaline phosphatase activity, expression of osteocalcin and bone morphogenetic protein 2, and inhibition of osteoclast differentiation [ 74 ].…”
Section: Possible Mechanisms Of Endocrine Disruptor Effect On Bone Tissuementioning
confidence: 99%
“…These components control the translocation and activation of glucose transporter proteins (primary effects of insulin) ( 133 ). ENMs can influence the signaling mechanism by interfering with the normal actions of cellular messengers ( 130 , 134 137 ).…”
Section: Endocrine Disrupting Engineered Nanomaterials (Edenms) and Mmentioning
confidence: 99%